Non-polar extracts of Nicotiana glauca (Solanaceae) induce apoptosis in human rhabdomyosarcoma cells - Musso, Florencia Antonella (2020)
Rhabdomyosarcoma (RMS) is the most common soft-tissue tumour in children andadolescents. It originates in normal skeletal muscle from myogenic cells that have failed tofully differentiate, and it usually has a poor prognosis. Current RMS therapy has manyadverse effects. Hence, new treatments are needed. Various pharmacological properties,such as analgesic, antineoplastic, antimicrobial, and antiparasitic properties, have beendemonstrated in species of the Solanaceae family. We performed ethanolic extraction fromleaves of Nicotiana glauca (Solanaceae), and the extract was successively partitioned withn-hexane, chloroform, and ethyl acetate. We evaluated the effects of extracts on RMScells, and we found that the extracts trigger apoptosis. By bio-guided fractionation assays,we identified the apoptotic agents. Morphological assessment after apoptotic cell inductionof cultured cells, mitochondrial and nuclear morphology by Mitotracker, and 4,6-diamidino-2-phenylindole (DAPI) staining, respectively, were analysed in fluorescentmicroscopy. The capacity of the cells to migrate or proliferate was analysed by the Petitassay, followed by methylene blue staining. NMR and GC-MS spectrometry were used toidentify palmitic acid and scopoletin as the phytochemicals responsible for the observedeffects. These results indicate that these compounds are apoptotic inducers and they couldbe useful as chemotherapeutic agents against muscle tumours.